Managemen Komunikasi Krisis pada Penurunan Harga Tiket OTS Festival Musik Asian Sound Syndicate Vol 2 2023 - Indah Mutiara Nurjana; Nur’annafi Farni Syam Maella; Harliantara (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The numerous complaints, both directly and on Asian Sound Syndicate's social media, have called into question the reputation of the event organizer, Stellar Event. The purpose of this study is to determine the strategic process of crisis communication management implemented by Stellar Event in dealing with the crisis. This process was carried out to understand the problem of how to identify the crisis, analyze the crisis, and find strategies for unraveling the crisis that occurred due to the decision of Stellar Event to reduce OTS ticket prices for the Asian Sound Syndicate Vol 2 2023 music festival. The research method used in this study is descriptive qualitative research. Data collection was carried out through in-depth interviews with the Project Manager, Head of Creative, and Head of Ticketing System & Ground Handling System. The results of the study indicate that in maintaining the good name and reputation of Stellar Event, they implemented an adaptive strategy in accordance with crisis management theory. This strategy was carried out through compromise and negotiation with ticket buyers, by upgrading class tickets, providing popcorn snacks, and ushering ticket buyers who protested, so that buyers received profitable privileges. In implementing this strategy, Stellar Events used the crisis as an opportunity to evaluate preparations for the second day of the music festival and anticipate if a similar crisis occurs.